Wellbeing in the aftermath of floods. (January 2017) - Walker-Springett, Kate; Butler, Catherine; Adger, W. Neil
Abstract: The interactions between flood events, their aftermath, and recovery leading to health and wellbeing outcomes for individuals are complex, and the pathways and mechanisms through which wellbeing is affected are often hidden and remain under-researched. This study analyses the diverse processes that explain changes in wellbeing for those experiencing flooding. It identifies key pathways to wellbeing outcomes that concern perceptions of lack of agency, dislocation from home, and disrupted futures inducing negative impacts, with offsetting positive effects through community networks and interactions. The mixed method study is based on data from repeated qualitative semi-structured interviews (n=60) and a structured survey (n=1000) with individuals that experienced flooding directly during winter 2013/14 in two UK regions. The results show for the first time the diversity and intersection of pathways to wellbeing outcomes in the aftermath of floods. The findings suggest that enhanced public health planning and interventions could focus on the precise practices and mechanisms that intersect to produce anxiety, stress, and their amelioration at individual and community levels. Highlights: Presents new mixed methods data from populations affected by floods. Examines in-depth key social factors that contribute to wellbeing impacts. Wellbeing is strongly affected by perceptions of agency and futures. Community connections provide an important protective element for wellbeing. Institutional responses positively and negatively affect responses at other scales.